Financial development convergence: New evidence for the EU - Dilara Kılınç; Ünal Seven; Hakan Yetkiner (Central Bank Review, 2017)
This paper aims to investigate whether the banking and stock market measures among European Union countries have been subject to a convergence process in order to verify whether the transition from the European Monetary System to the Single Currency in the last five decades have led to the integration of financial markets. We show that banking and stock market measures tend to converge across the EU over time, and the process is even improved by controlling for the quality of country level institutions and a range of macroeconomic variables. We conclude that there is a degree of success in the financial integration process of EU countries and therefore recommend that the EU accelerates financial integration to completion rather than to slowing the process.